(3bUjOI GHf cejd GdefUhQj TeS GdOjf aj eOM GdfHj Udi Gddg Ydjg hSdes - (3TeS GdOjf eMeO Hf CMeO Hf cejd GdefUhQjs
(3ChdgG (B:s
(3CQHY bUGFO GdChdi ddbGOQj heWdYgG(B: (3HOJ aCQJc TeS GdeWdYjf aJGg CSgQJ HGdeWd Yjfj s
(3BNQgG (B:s
(3Udi Ydjc Edg GdYQT aGfgedJ Edi GdMLGR hMGOj GdQcH jMOjg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3CQHY bUGFO(B: (3GdChdi ddbGOQjs
(3hGdKGfjI hGdQGHYI ddfhGLjs
(3hGdKGdKI dGHf cejds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B105 s
Keywords: (3GdCOHs